2022
DOI: 10.3390/f13050775
|View full text |Cite
|
Sign up to set email alerts
|

Inherent Water-Use Efficiency of Different Forest Ecosystems and Its Relations to Climatic Variables

Abstract: Inherent water-use efficiency (IWUE) is a vital parameter connecting the carbon and water cycles. However, the factors influencing the IWUE in different forest ecosystems are still a subject of debate. In this work, FLUXNET platform measurements of 67 forest sites were used to detect trends of the IWUE of four forest ecosystems, namely deciduous broadleaf forests (DBF), evergreen broadleaf forests (EBF), needle-leaf forests (ENF), and mixed forests (MF). The IWUE differed significantly among different forest e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…The ecosystems of southern South America, where incoming weather fronts originate directly over the southern Pacific Ocean, have not been exposed to industrial pollution, in contrast to the forests of the Northern Hemisphere, so the nitrogen cycle in the study area has been defined as unpolluted (Hedin et al, 1995). Annual values of WUE showed a wide variation in the forest (between 1.94 and 3.29 g C kg −1 H 2 O) compared to the interannual variability reported for an oldgrowth subtropical forest over 7 years (between 1.70 and 1.98 g C kg −1 H 2 O; Liu et al, 2017), which may be explained by the occurrence of an extremely dry year in our study site in 2016 (Garreaud, 2018), which was associated with the highest WUE value, followed by a wet year in 2017 that was associated with the lowest WUE value. Based on measurements of NEE the forest was a net sink, while the peatland was a small source, which is consistent with an estimation made by Perez-Quezada et al (2021b), who showed that fire in this area has strong and long-term effects on the forest greenhouse gas balance, by converting the forest into an anthropogenic peatland.…”
Section: Seasonal and Annual Variation Of The Fluxes And Water Use Ef...mentioning
confidence: 99%
See 1 more Smart Citation
“…The ecosystems of southern South America, where incoming weather fronts originate directly over the southern Pacific Ocean, have not been exposed to industrial pollution, in contrast to the forests of the Northern Hemisphere, so the nitrogen cycle in the study area has been defined as unpolluted (Hedin et al, 1995). Annual values of WUE showed a wide variation in the forest (between 1.94 and 3.29 g C kg −1 H 2 O) compared to the interannual variability reported for an oldgrowth subtropical forest over 7 years (between 1.70 and 1.98 g C kg −1 H 2 O; Liu et al, 2017), which may be explained by the occurrence of an extremely dry year in our study site in 2016 (Garreaud, 2018), which was associated with the highest WUE value, followed by a wet year in 2017 that was associated with the lowest WUE value. Based on measurements of NEE the forest was a net sink, while the peatland was a small source, which is consistent with an estimation made by Perez-Quezada et al (2021b), who showed that fire in this area has strong and long-term effects on the forest greenhouse gas balance, by converting the forest into an anthropogenic peatland.…”
Section: Seasonal and Annual Variation Of The Fluxes And Water Use Ef...mentioning
confidence: 99%
“…These three variables were also identified as the main drivers of ecosystem carbon and water fluxes for northern peatlands in Canada (Humphreys et al, 2006). Liu et al (2017) also found global radiation and vapour pressure deficit to be among the main drivers of GPP and ET in a subtropical forest in China, although they reported that precipitation and soil moisture were even more important.…”
Section: Main Environmental Drivers Of Carbon and Water Fluxesmentioning
confidence: 99%
“…The flux system is installed at a height of 40 m on the flux tower and equipped with primary sensors, including a three-dimensional ultrasound and CO 2 /H 2 O analyzer (IRGASON, Campbell Scientific Inc., Logan, UT, USA), a four-component radiation meter (CNR4, Kipp & Zonen, Delft, Netherlands), an air temperature and humidity sensor (HMP155A, Vaisala, Helsinki, Finland), and a soil heat flux plate (HFP01, Hukseflux, Delft, Netherlands). The six-layer gradient system is capable of measuring meteorological variables at different spatial heights (2,8,16,24,32, and 40 m) and soil depths (10,20,30,40,60, and 90 cm), utilizing sensors such as soil temperature sensors (TCAV, Campbell Scientific Inc., Logan, UT, USA), soil moisture sensors (CS616, Campbell Scientific Inc., Logan, UT, USA), wind direction sensors (020C, Met One Instruments Inc., OR, USA), wind speed sensors (010C, Met One Instruments Inc., OR, USA), a rain gauge (RG3-M, Oneset, MA, USA), and air temperature and humidity sensors (HMP155A, Campbell Scientific Inc., Logan, UT, USA). The profiling system, primarily composed of Atmospheric Profile 200 (AP200, Campbell Scientific Inc., Logan, UT, USA) and air intake components, measures the concentrations of CO 2 and H 2 O in the air at six observation levels (spatial heights of 2, 8, 16, 24, 32, and 40 m).…”
Section: Data Collection and Processingmentioning
confidence: 99%
“…In forest ecosystems, the variation in WUE is particularly complex, as it is influenced by numerous interacting ecological and environmental factors [4]. Based on our current knowledge, among different types of forest ecosystems, the WUE of evergreen coniferous forests is the highest, followed by deciduous coniferous forests, evergreen broad-leaved forests, and finally, deciduous broad-leaved forests [14][15][16]. As one of the important forest types, the research on WUE in mixed coniferous-broadleaf forests is relatively scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we should pay attention not only to the direct benefits that forests can provide in terms of wood, biochar, and the other forest products, but also to the indirect benefits of ecosystem services with respect to climate regulation, water source conservation, and flood disaster retention and reduction, all of which depend on the dynamic relationship between forest and water ( Bosch and Hewlett, 1982 ). To sum up, it is necessary to conduct in-depth research on forest eco-hydrological processes and to evaluate their environmental benefits, at whose core is the relationship between vegetation cover and runoff, to elucidate the mechanisms underpinning allocation of crown-intercepted precipitation, water retention by litter, soil water infiltration and storage, terrestrial evapotranspiration, and so on, among forest strata such as vegetation crown, ground covering layer of plants, and the soil ( Wang et al., 2001a ; Xian et al., 2014 ; Lu et al., 2015 ; Liu et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%